Corrigendum: Exploring the Use of Virtual Reality for the Delivery and Practice of Stress-Management Exercises (Front. Psychol., (2021), 12, 10.3389/fpsyg.2021.640341) - Soh, Desmond Jun Hong (Frontiers Media S.A., 2022)
10.3389/fpsyg.2021.752647